Keberagamaan dan Perilaku Sosial Remaja Akibat Perceraian Orang Tua (Studi Kasus di Kecamatan Teluk Nibung Kota Tanjung Balai) - Fikri, Muhammad; Abbas, Mardhiah (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2025)
Divorce has a negative impact on the family, especially for children's development. Circumstances that occur after divorce affect the psychology and socio-religious life of children, in this case teenagers. Adolescence is a period full of mental turmoil, namely a period of transition or on a rocking bridge, which connects childhood which is full of dependency, with adulthood which is mature and independent. Along with the pace of development of the times, people's lives today are felt to be increasingly complex. The problems that arise are of course very varied, the type and nature of which range from personal problems related to association, lifestyle, to religious behavior which is closely related to individual beliefs, including adolescents. Teenagers are the next generation of the nation who are expected to be able to generate high integration in social life in society, while the personality of a teenager determines his social and religious behavior, both specifically in the family environment and in general in the community environment. In adolescence, they need a figure that they can make an example of, namely their parents. Thus, it is possible that the occurrence of divorce will affect the social and religious behavior of adolescents. Divorce that occurs in the community has an impact on children as victims in daily life. Based on the results of the research, children who are victims of divorce initially feel insecure when hanging out with friends in the neighborhood or at school. However, this situation will gradually change because children feel used to it and their friends can also understand it.